VYSHYVANKA AS A TEXT: METHODOLOGICAL PRACTICES IN UKRAINIAN LANGUAGE CLASSES - ANTOFIYCHUK, Alla (Mountain School of Ukrainian Carpaty, 2025)
The article explores the embroidered shirt (vyshyvanka) as a cultural and semiotic text that can be effectively integrated into Ukrainian language lessons. The study substantiates the relevance of using embroidery as a verbal-visual resource that fosters the development of students’ linguistic-cultural, emotional-value, and creative linguistic competencies. The research presents a range of methodological practices, including tasks focused on linguistic-cultural interpretation of ornament, working with poetic texts as verbal analogues of embroidery, creative writing from the perspective of vyshyvanka, vocabulary exercises based on ethnocultural lexicon, as well as project-based and integrated lessons. Special attention is paid to the development of exercises that stimulate observation, associative thinking, linguistic imagination, and personal reflection on tradition. The author highlights the possibilities for students of creating visual and verbal texts-collages, infographics, booklets, and family stories that interpret ornamental patterns as linguistic signs. The article also emphasizes the importance of integrating linguistic and artistic activities to promote a sense of continuity, respect for national culture, and an understanding of language as a space of identity. The practical recommendations provided can be used by Ukrainian language teachers to design interactive, culturally enriched lessons that foster not only language skills but also meaningful engagement with the traditional textual heritage of the Ukrainian people.